2021
DOI: 10.3390/cancers13225740
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Malignant Transformation in 3173 Subjects with Histopathologically Confirmed Oral Lichen Planus: A 33-Year Cohort Study in Northern Italy

Abstract: Background: Oral lichen planus (OLP) is considered an oral potentially malignant disorder. The aim of our study was to estimate the risk for oral cancer in patients diagnosed with OLP. Methods: A population-based cohort study between January 1988 and December 2020 at one hospital in Northern Italy was performed. The primary endpoint of the study was that of the histopathological diagnosis of oral cancer during the follow-up period. Results: The study population comprised 3173 patients. During the follow-up per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 31 publications
1
27
0
Order By: Relevance
“…Recently, Arduino et al [ 32 ] have reported that patients with fewer oral sites involved by OLP lesions presented across the years a higher risk of cancer development because such patients are less likely to undergo routine oral consultations. Therefore, although the painful symptomatology is associated with an impaired quality of life, the presence of oral symptoms could be protective in that pain is the most important motivation for OLP patients to seek help and treatment from a clinician [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Arduino et al [ 32 ] have reported that patients with fewer oral sites involved by OLP lesions presented across the years a higher risk of cancer development because such patients are less likely to undergo routine oral consultations. Therefore, although the painful symptomatology is associated with an impaired quality of life, the presence of oral symptoms could be protective in that pain is the most important motivation for OLP patients to seek help and treatment from a clinician [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several factors may limit the life expectancy of patients with LP[ 94 , 95 ]. Oral squamous cell carcinoma is one of them, as oral LP is widely regarded as a precancerous condition, even though the exact rate of malignant transformation is a matter of debate[ 55 , 96 - 99 ].…”
Section: Main Bodymentioning
confidence: 99%
“…Compared to other OPMDs, 4–8 OLP has a lower MT rate potential, but it has been estimated that OLP has a cumulative MT rate of 1.4% (99% CI 0.9–1.9), with a yearly MT rate of 0.28% 9 . Arduino et al in a recently published study 10 conducted on 3173 OLP patients with a long‐term follow‐up confirmed this conclusion. Although there is a substantial amount of research on progression to cancer, 11–13 a specific analysis regarding SCC developed on OLP lesions and its differences with SCC in patients without a history of OLP has not been investigated so far.…”
Section: Introductionmentioning
confidence: 98%